2019
DOI: 10.3389/fpsyg.2019.00717
|View full text |Cite
|
Sign up to set email alerts
|

Should Employers Invest in Employability? Examining Employability as a Mediator in the HRM – Commitment Relationship

Abstract: This study investigates the relationship between perceived investments in Human Resource (HR) practices and workplace commitment, from the perspective of social exchange theory. An innovative feature is that we introduce perceived employability as a potential mediator, thus bringing in a career perspective: our argument is that perceived investments in HR practices promote feelings of employability, which then create workplace commitment. Based on a 6-week follow-up sample ( N = 437) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 57 publications
(87 reference statements)
7
58
0
2
Order By: Relevance
“…As regards the organizational level, Akkermans et al (2019) already identified employability as an explanatory mechanism in the HR practices – outcome (i.e., organizational commitment) relationship. In a similar vein, De Coen et al (2015) showed that self-awareness and adaptability negatively relate to older workers’ intention to retire via multiple paths, including enhancing self-directedness that, in turn, leads to a higher self-perceived employability.…”
Section: Perceived Employability As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the organizational level, Akkermans et al (2019) already identified employability as an explanatory mechanism in the HR practices – outcome (i.e., organizational commitment) relationship. In a similar vein, De Coen et al (2015) showed that self-awareness and adaptability negatively relate to older workers’ intention to retire via multiple paths, including enhancing self-directedness that, in turn, leads to a higher self-perceived employability.…”
Section: Perceived Employability As a Mediatormentioning
confidence: 99%
“…We take the opposite point of view by focusing on why people want to work until their official retirement age instead of retiring early. In addition to studying the effects of factors at the individual (training/education) and at the job level (learning value of the job) respectively, we decided to include a factor at the organizational level (organizational career management practices) as well, as prior research has shown that organizational HR practices may influence employee attitudinal and behavioral outcomes (Guest, 1999; Gratton and Truss, 2003; Akkermans et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This length of time lag is in line with the recommendations of Dormann and Griffin (2015) of a relatively short time lags in survey research focusing on psychosocial work characteristics and worker outcomes. Moreover, a time lag of 6 months was considered appropriate as previous studies have demonstrated that the outcomes included in this study can fluctuate in rather short periods (De Lange et al, 2004;Zacher et al, 2014;Akkermans et al, 2019;Rudolph and McGonagle, 2019;Rudolph and Zacher, 2020). The first questionnaire (T1) was sent to the participants between November 2017 and the end of January 2018, the second questionnaire (T2) between June 2018 and the middle of August 2018.…”
Section: Design Of the Study And Proceduresmentioning
confidence: 99%
“…Another relevant concept is professional development, which refers to employees "perceptions of their employment possibilities in the internal and/or external work market [38] " . This configures in function of a norm of reciprocity between the organization and the individuals or work groups, according to the resources invested by them.…”
Section: Health From the Organizational Levelmentioning
confidence: 99%
“…Pride is one of the pillars most perceived by employees [30]. • The concept of development: a set of practices for the social exchange of work (resources) between employees, work teams and the organization for the benefit of the skills required by the working environment [38].…”
Section: To the Best Places To Workmentioning
confidence: 99%